(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2011)
The paper suggests an analysis concerning the supposed compatibility between Frege’s intuitive criterion for difference (i.e. if it is possible, for a subject S, to believe p and not believe q, then the content of p is different from the content of q) and an externalist perspective in determining the content of beliefs. Although initially endorsing the fregean criterion, Burge (1979a) claims that the individual competence is negligible for matters concerning reference: the competence of the linguistic community is what solely must be taken into account for it. But this inevitably leads to the rejection of Frege’s criterion. The discussion pursues Burge’s thought, showing how even a more sophisticated point of view, such as Burge (1982), leads to the same conclusion, nonetheless depicting Burge’s form of externalism as thoroughly problematical.